THE EFFECT OF CLIMATE VARIABILITY ON POLLEN PRODUCTIVITY, AD 1975-2000, RECORDED IN A SPHAGNUM PEAT HUMMOCK - Sjogren P.; van Leeuwen Ja.F.N.; van der Knaap W.O.; van der Borg K. (My University, 2006)
Pollen accumulation rates and pollen percentages from a Sphagnum peat hummock in the Jura Mountains were used to determine past pollen deposition. Post-bomb calibrated radiocarbon dates allowed estimations of annual variability in pollen productivity AD 1975-2000. Percentages of abundant taxa were modified (downweighted) to reduce the influence of plant cover, mean pollen productivity, and interdependence of the variables. Significant correlations with seasonal climatic parameters (tested with simple linear regression) were found both for pollen accumulation rates and for modified pollen percentages. Winter temperature is an important factor for pollen productivity of several tree species. The climatic effect on the modified pollen assemblage is best explained by a wet/warm to cold/dry gradient, but seasonal influence is considerable (ordination by PCA, RDA). Modified pollen percentages showed similarities in annual fluctuations between sites in the Jura Mountains, the Western Alps and the Eastern Alps.
Keywords: ANNUAL RESOLUTION; CLIMATE; POLLEN PRODUCTIVITY; SPHAGNUM HUMMOCK